Analisis Daya Gabung Umum dan Daya Gabung Spesifik Galur Superior Jagung Provit-A - HG, M. Yasin; Mas’ud, Syahrir; Faesal, Faesal (Jurnal Penelitian Pertanian Tanaman Pangan, 2013)
The experiments were conducted to study the genetic yield potential of six inbred lines and to develop superior hybrid of Provit-A maize. A diallel cross combinations including parents were conducted at Maros experimental farm in two seasons of 2009. The first experiment was to generate diallel F1’s between inbred parents, followed by the evaluation of General Combining Ability (GCA) and Specific Combining Ability (SCA) among inbred lines. The experiment used a randomized complete block design with two replications, tested 21 genotypes consisting of six parents and 15 F1 crosses. Griffing’s model II was applied without reciprocal crosses, and the data were analyzed using the MSTATC program. The second experiment was conducted from August to November 2009. The results indicated that GCA and SCA effects were significant. The best SCA was obtained from cross of KUI Carotenoid Syn-FS25-3-2-B-BxCML305-B-B (P4xP6) and from KUI Carotenoid Syn-FS25-3-2-B-BxCarotenoid Syn3-FS5-1-5-B-B (P4xP5). Mid parent heterosis (MPH) was 254% and 260% and yield was 11.0 t/ha. The best GCA was indicated by KUI Carotenoid Syn-FS25-3-2-B-B (P4).